HMGB1 Mediated Inflammation and Autophagy Contribute to Endometriosis - Huang, Jingying; Chen, Xuan; Lv, Yuchun (Frontiers in Endocrinology, 2021)
Aim High mobility group box (HMGB)-1 has been implicated in endometriosis due to the important regulatory roles of inflammation in endometriosis. The aim of the present study was to explore the roles of HMGB-1 in endometriosis and to elucidate the underlying mechanism. Methods Endometrial specimens were collected from women with endometriosis and healthy volunteers. Immunohistochemistry staining was used to determine the expression patterns and localization of HMGB-1 in the normal, eutopic and ectopic endometrial tissues. Western blotting and qRT-PCR were used to determine the mRNA and protein levels of inflammatory cytokines [interleukin (IL)-6, tumor necrosis factor (TNF)-α and IL-1β], autophagy-related markers [beclin-1, autophagy-related (atg)13, microtubule-associated protein light chain (LC)3-I, LC-II and p62] and HMGB-1, respectively. Spearman’s rank correlation analysis was employed to investigate the correlation between HMGB-1 with inflammatory cytokines and beclin-1. Besides, human endometrial stromal cells (HESCs) were isolated from ectopic endometrium and subsequently transfected with shRNA against HMGB-1. After the transfected cells were subjected to hypoxia, ELISA was used to determine the levels of HMGB-1 and inflammatory cytokines in the cell supernatant. Western blotting was used to determine the expression levels of autophagy-related markers in the cells. Results Positive correlations were observed between HMGB-1 and the inflammatory cytokines. In addition, a positive correlation was also identified between HMGB-1 and beclin-1 in the ectopic endometrium. Further results demonstrated that autophagy-related markers beclin-1, atg13 and p62 were significantly upregulated in the ectopic endometrium. In addition, HMGB-1 knockdown suppressed the levels of inflammatory cytokines IL-6, TNF-α and IL-1β and autophagy-related markers beclin-1 and atg13, while upregulated p62 in HESCs under hypoxic condition. Conclusion Knockdown of HMGB-1 under hypoxic condition regulated inflammatory cytokines and autophagy-related markers. HMGB-1 might contribute to the development of endometriosis in part through regulating inflammatory response and autophagy.